2017
DOI: 10.2147/nan.s105134
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of estrogen in CNS injuries: insights from animal models

Abstract: Among the estrogens that are biosynthesized in the human body, 17β-estradiol (estradiol or E2) is the most common and the best estrogen for neuroprotection in animal models of the central nervous system (CNS) injuries such as spinal cord injury (SCI), traumatic brain injury (TBI), and ischemic brain injury (IBI). These CNS injuries are not only serious health problems, but also enormous economic burden on the patients, their families, and the society at large. Studies from animal models of these CNS injuries p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 109 publications
0
46
0
1
Order By: Relevance
“…Interestingly, MBP protein and mRNA was also recovered in the hippocampus and neocortex, suggesting possible myelin‐protective effects of endogenous steroids. Previous studies have conclusively demonstrated the promyelinating, neuroprotective and anti‐inflammatory effects of sex steroids in the CNS . In cuprizone demyelination, the combined treatment with progesterone and oestradiol of young mice counteracts myelin loss, whereas single progesterone treatment increases the number of mature oligodendrocytes, its precursors (OPCs) and myelin proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MBP protein and mRNA was also recovered in the hippocampus and neocortex, suggesting possible myelin‐protective effects of endogenous steroids. Previous studies have conclusively demonstrated the promyelinating, neuroprotective and anti‐inflammatory effects of sex steroids in the CNS . In cuprizone demyelination, the combined treatment with progesterone and oestradiol of young mice counteracts myelin loss, whereas single progesterone treatment increases the number of mature oligodendrocytes, its precursors (OPCs) and myelin proteins .…”
Section: Discussionmentioning
confidence: 99%
“…We argue that, despite profound dichotomy between basic science and clinical studies, E2 is ideally suited to be developed as a broad-spectrum neuroprotectant if its action can be restricted to the CNS, that is, to the site of action to avoid undesirable peripheral hormonal burdens. Since neurotrauma triggers a cascade of biochemical events leading to further damages decreasing thereby the chance of appreciable functional recovery [17,20,102,103], chronic pharmacotherapeutic interventions should be considered in the context of translational research. This, on the other hand, brings about critical considerations for safety and efficacy, which highlights the need for brain-selective (or in general CNS-selective) neurotherapy, considering both a preventative and a curative modality.…”
Section: Cns-selective Estrogen Neurotherapymentioning
confidence: 99%
“…Among estrogens and estrogenic compounds, E2 also is the best-known estrogen to be used as a powerful neuroprotective agent in various in vitro and preclinical animal models of neurodegeneration impacting the central nervous system (CNS) [16][17][18][19][20]. It is important to emphasize, though, that E2 has a large array of other beneficial effects in the CNS, including regulating body temperature, enhancing cognition and memory and ameliorating neuropsychiatric conditions in both females and males [7,11,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is a common steroidal sex hormone in women. Four natural estrogens are biosynthesized: estrone (E1), estradiol (E2), estriol (E3), and estetrol (E4) (4,5). E1 has a hydroxyl group at the C3 position, and a ketone group at the C17 position (5).…”
Section: Introductionmentioning
confidence: 99%
“…Four natural estrogens are biosynthesized: estrone (E1), estradiol (E2), estriol (E3), and estetrol (E4) (4,5). E1 has a hydroxyl group at the C3 position, and a ketone group at the C17 position (5). It is an agonist of the estrogen receptors ERα and ERβ but is considered to be a weak estrogen (4).…”
Section: Introductionmentioning
confidence: 99%